“Ninguém dá emprego às pessoas TRANS”: divisão (CIS)generificada do trabalho e as experiências de pessoas TRANS em Juazeiro do Norte – CE - Silva, Poliana Machado Gomes da (2025)
This thesis aims to analyze how the (cis)gendered division of labor is expressed in the work experiences of trans people in Juazeiro do Norte - CE. Furthermore, it specifically aimed to: identify where trans people from Juazeiro are in the (cis)gendered division of labor; understand the perceptions about work and the status of passability in the (cis)gendered division of labor based on the experiences of trans people; reflect on how transphobia affects the work of trans people. To this end, a qualitative approach was carried out and intersectionality was used as a methodological and theoretical-political tool. As data collection techniques, field research, semi-structured interviews with eight trans people from Juazeiro and the field diary instrument were used. The (cis)gendered division of labor was problematized, which produces not only supposed truths about gender, but also about work. It was found that the intersection between prohibitions and transphobic violence suffered by trans interlocutors in their daily lives contributes to the processes of marginalization in their work contexts. It was found that, for the most part, trans people are positioned in informal work, in care work, in invisible occupations with the most precarious and unstable income, with little or no social protection. When they are in formal employment, they perform socially devalued and invisible work. It was found that passability should not be understood only as a mechanism of assimilation that reproduces cisgender and heterosexuality as norms, but is also a strategy used by trans people to avoid transphobic violence, to form alliances in the search for the guarantee of rights, for insertion in the formal job market, as a matter of survival and self-care. Despite this, not all trans people aspire to passability. Finally, access to formal employment does not eliminate gender disparities and violations of rights, nor does it ensure the conditions for inclusion, permanence, success and safety in this context.